Photochemical growth of metal nanoparticles on domain patterned ferroelectric surfaces - Tiwari, Divya (Cranfield University, 2009)
In this work, the growth of metal nanoparticles on domain patterned ferroelectric Pb(ZrxTi1-x)O3 and LiNbO3 by photochemical reaction is demonstrated. The photochemical properties and phenomena occurring on the surface of Pb(ZrxTi1-x)O3 and LiNbO3 under ultraviolet illumination are investigated. Ferroelectric materials possess a reversible spontaneous polarisation that has an effect on photochemical reactivity of a surface. Since the spontaneous polarisation is reversible, a desired pattern can be drawn on a ferroelectric surface in the form of domains. A combination of domain patterning and domain specific surface reactions can lead to fabrication of complex nanostructures. It is found that on a PZT (30/70) thin film, under UV irradiation, metal deposition occurred only on C + domains and no deposition occurred on C - domains. Hence, the chemical reactivity of ferroelectric surface was found to be dependent on the polarisation of domain that is underlying the surface. Annealing of PZT samples at high temperatures alters the defect concentration of the PZT as shown by an increase in the deposition of silver on the surface. When the PZT samples were annealed in air at temperatures ranging from 530-690°C the silver deposition increased by more than 150% and the size of deposited silver clusters increased by four times. The photochemical properties of PZT thin films of different compositions PbZr0.3Ti0.7O3, PbZr0.52Ti0.48O3 and PbZr0.7Ti0.3O3 were investigated by undertaking silver nanocluster deposition experiments. The composition of PZT film (Zr/Ti ratio) affects silver deposition such that on PbZr0.3Ti0.7O3 silver deposits only on C + domains, whereas PbZr0.52Ti0.48O3 and PbZr0.7Ti0.3O3 experience deposition on both C + and C - domains. This difference in silver deposition pattern is shown to be due to the difference in width of the space charge region and bandii gap of the three samples. The impact of size of poled pattern on silver deposition at the surface is shown. It is found that for smaller size of C + domains (smaller than 1 μm) the amount and size of deposited silver decreased with the decrease in domain size. On a PZT surface, formation of spherical, triangular and hexagonal nanoplates of gold via photoreduction has also been demonstrated. Silver cation reduction on C + and C - domains of ferroelectric lithium niobate (LN) by photochemical and photoelectric process is demonstrated. The interaction of photoelectric and domain dependent influences can be observed in LiNbO3 due to the low electron affinity (ca 1.1-1.5eV). The impact of composition of LN on the photoreduction of silver has been shown. It is found that the photochemical reactivity of MgO-doped LN is significantly higher as compared to non-doped LN. The energy and intensity of incident photon is also found to have an impact on the photoreduction of silver on LN surface. In addition to this, deposition of Al and Mn nanoparticles on LN surface by means of photoreduction reaction has been demonstrated. It is shown that for a metal to photoreduce on C + domain of a ferroelectric material, the reduction potential of the metal has to be within the band-gap of the material. It is shown that under atmospheric conditions, it is possible to selectively adsorb molecules of opposite charge on the surface of LN due to uncompensated polarisation charge.